2019
DOI: 10.18087/cardio.2019.12.n733
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in Patients on Dialysis Therapy: Epidemiology, Prognosis and Choice of Anticoagulant Therapy

Abstract: The review presents data on the prevalence of atrial fibrillation in patients on dialysis therapy. It is shown that dialysis-dependent patients with non-valve atrial fibrillation prognosis is extremely unfavorable, significantly increased risk of death due to both ischemic and hemorrhagic complications. Scales to assess the risk of thromboembolic and hemorrhagic complications in patients with atrial fibrillation on program dialysis are not validated. The lack of data from randomized clinical trials makes it mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
1
0
0
Order By: Relevance
“…The mortality rate is high in regular dialysis patients, and it was about 9% per year according to the Japanese Society for Dialysis Therapy (24). Additionally, reports showed that AF in dialysis patients was associated with a higher mortality rate (2,5,25). In the present study, all-cause mortality after CA was significantly higher among HD patients (12.0%) compared to control group (1.0%).…”
Section: Discussionsupporting
confidence: 44%
“…The mortality rate is high in regular dialysis patients, and it was about 9% per year according to the Japanese Society for Dialysis Therapy (24). Additionally, reports showed that AF in dialysis patients was associated with a higher mortality rate (2,5,25). In the present study, all-cause mortality after CA was significantly higher among HD patients (12.0%) compared to control group (1.0%).…”
Section: Discussionsupporting
confidence: 44%